Examination of impulsiveness and aggression in substance abuse - KARACA, SEMRA (KLINIK PSIKIYATRI DERGISI, 2020)
Objective: The use of addictive substances is usually related with many problems physical, mental and social aspects. The present study aims to examine levels of impulsiveness and aggression and the relationships between impulsiveness and aggression in substance abuse. Method: This cross-sectional study was conducted in an alcohol and addiction treatment center of a psychiatric hospital in Istanbul. In order to conduct this study, ethical committee permission was obtained from the Ethics Committee of Marmara University and official permission was obtained from hospital. The sample size was calculated using a statistical formula and the study was conducted with 126 patients. Data was collected by Demographic Information Form, Barrat Impulsivity Scale (BIS-11) and Buss Pery Aggression Scale (BPAS). The data was analyzed using descriptive statistical analysis Shapiro-Wilk test, Student's t test, Mann-Whitney U, One-way ANOVA, Kruskal Wallis and Pearson correlation analysis. Results: 92.9 % male of patients, 58.7 % were single, 40.5% high school graduates and mean age was 29.53 +/- 8.20. BIS-11 total score of the patients was 63.86 +/- 8:47. BPAS total score of the patients was 50.70 +/- 20.77. Statistically significant positive peer relationships were found between averages of BIS-11 total scores, BPAS total scores and all sub-scale scores (between BIS11 total scores and BPAS total scores r=0.299, p=0.001; physical aggression r=0.225; p=0.012; verbal aggression r=0.212, p=0.018; anger r=0.191, p=0.033; hostility r=0.373, p=0.001). Discussion: In this study, the majority of participants was male. Of substance abuse, it is seen that increased impulsivity, aggression increases overall score.
Keywords: Substance abuse; impulsiveness; aggression; ALCOHOL; ANGER; ADDICTION; BEHAVIOR; AGE; PERSONALITY; DISORDER; HEROIN